THE EFFECTIVENESS OF USING WORD WALL STRATEGY TO IMPROVE STUDENTS’ WRITING SKILL IN DESCRIPTIVE TEXT AT ISLAMIC BOARDING SENIOR HIGH SCHOOL AN-NUR MUARO JAMBI - Nedia Efina Wandefit; Faiqah Mahmudah; Dewi Hasanah; Desti Angraini (JR-ELT (Journal of Research in English Language Teaching), 2023)
This study discussed about using Word Wall Strategy on students’ writing achievement at Islamic Boarding Senior High School An-Nur Muaro Jambi. The goals of the research are to find out the effect of Word Wall Strategy on Students’ writing achievement after being taught by using Word Wall Strategy and to find out significant different between students’ who are taught by using Word Wall Strategy and those who are not. This research method is quantitative research.Sample of the research were 60 students which experimental class was 30 students and control class 30 students. The data collection is used pre-test and post-test. The instrument for collecting data was a test. After analyzing the data, the writer got; (1) The students’ achievement in writing descriptive text by Word Wall Strategy got the mean 76.00 and standard deviation was 8.06; (2) The students’ achievement in writing descriptive text by using conventional method got the mean 62.47 and standard deviation was 7.30. The value of tobserved was 6.564 and that of ttable was 2.009. So the value of tobserved was higher than that of ttable. It means that there was significant effect of using Word Wall strategy on students’ achievement in writing descriptive text.